Prawne i etyczne gwarancje wykonywania obowiązków biegłego psychiatry w procesie karnym: [Legal and ethical guarantees of performing duties by an expert in psychiatry in criminal proceedings] (Studia Prawnicze / The Legal Studies, 1983)
The criteria of appointing experts for criminal proceedings are their professional qualifications and impartiality. The goal of the work is to define these criteria in relation to experts in psychiatry. The interpretation of legal provisions (especially of art. 179 of the code of criminal procedure) has been accompanied by considerations from the field of deontology and ethics of psychiatric expert opinions.Doctors suggest that only those doctors clinicians who have completed the second post-graduate course in psychiatry may be entered on the list of court experts, which seems to be right. In the proceedings they should conduct psychiatric examination only; conducting psychological and neurological examinations at the same time is beyond their competence. The impartiality of an expert is partially ensured by formalized premises of exclusion defined in art. 179 § 1 of the code of criminal procedure. The following situations should be added here: mutual relations of experts (kinship, marriage, subordination in service), incorrect relations in the course of examination (gross disproportion of authorities, "formal" participation in the examination), close relation of an expert to other than the accused participants in the proceedings (public prosecutor), involvment of an expert in the case outside the court (expressing private opinions on the case for press, radio, television), etc.The scope of professional secrecy of doctors has been considered on the basis of deontological norms, having assumed that the information obtained from the accused in the course of the examination which is not absolutely necessary for the proper motivation of the diagnosis should be considered secret.The scope of diagnostic examinations (in particular neurophysical ones) admissible in the psychiatric expert opinion has also been considered.It has been assumed, on the basis of art. 65 of the code of criminal procedure and deontological principles of therapy; that only those examinations may be conducted which do not constitute a challenge to the accused health. Diagnostic methods consisting in narrowing the consciousness of the accused by pharmacological means have been considered in conflict with the ethics.